Cell Surface Proteins for Enrichment and In Vitro Characterization of Human Pluripotent Stem Cell-Derived Myogenic Progenitors. (24th February 2022) - Tey, Sin-Ruow; Mueller, Madison; Reilly, Megan; Switalski, Colton; Robertson, Samantha; Sakanaka-Yokoyama, Mariko; Suzuki, Masatoshi
Abstract : Human myogenic progenitors can be derived from pluripotent stem cells (PSCs) for use in modeling natural and pathological myogenesis, as well as treating muscle diseases. Transgene-free methods of deriving myogenic progenitors from different PSC lines often produce mixed populations that are heterogeneous in myogenic differentiation potential, yet detailed and accurate characterization of human PSC-derived myogenic progenitors remains elusive in the field. The isolation and purification of human PSC-derived myogenic progenitors is thus an important methodological consideration when we investigate the properties and behaviors of these cells in culture. We previously reported a transgene-free, serum-free floating sphere culture method for the derivation of myogenic progenitors from human PSCs. In this study, we first performed comprehensive cell surface protein profiling of the sphere culture cells through the screening of 255 antibodies. Next, we used magnetic activated cell sorting and enriched the cells according to the expression of specific surface markers. The ability of muscle differentiation in the resulting cells was characterized by immunofluorescent labeling and quantification of positively stained cells. Our results revealed that myotube-forming cells resided in the differentiated cultures of CD29 +, CD56 +, CD271 +, and CD15 – fractions, while thick and multinucleated myotubes were identified in the differentiated cultures from CD9 + and CD146 + fractions. We found that PAX7 localization to the nucleus correlates with myotube-forming ability in these sorted populations. We also demonstrated that cells in unsorted, CD271 +, and CD15 – fractions responded differently to cryopreservation and prolonged culture expansion. Lastly, we showed that CD271 expression is essential for terminal differentiation of human PSC-derived myogenic progenitors. Taken together, these cell surface proteins are not only useful markers to identify unique cellular populations in human PSC-derived myogenic progenitors but also functionally important molecules that can provide valuable insight into human myogenesis.